Metal Oxides/Carbon Felt Pressure Sensors with Ultra‐Broad‐Range High Sensitivity. Issue 3 (5th December 2021) - Wang, Xiu‐man; Chai, Yujun; Wang, Ze‐ping; Yu, Jiabing; Chen, Xianping; Wong, Ching Ping
Abstract: Flexible piezoresistive pressure sensors have been extensively used in the field of wearable sensors. However, it is difficult to achieve both ultrahigh sensitivity and pressure range, with traditional pressure sensors. Therefore, a new Co3 O4 /carbon felt pressure sensor is proposed here, where Co3 O4 as nanospacer provides low initial current without loading. Carbon felt with a rough surface as a flexible substrate provides a high output current under loading and extends the measurement range of the pressure sensors. The high sensitivity of the pressure sensors can be achieved with a low initial current and high output current. The Co3 O4 /carbon felt pressure sensors exhibit high sensitivity (243 kPa −1 ), ultralow detection limit (1.3 Pa), fast response (14 ms), and broad range (up to 180 kPa) of measurements. These excellent performances indicate that the Co3 O4 /carbon felt pressure sensor has great potential for application in wearable, healthcare devices. Furthermore, this strategy can be extended to the fabrication of other metal oxides/carbon felt pressure sensors. Abstract : Metal oxides/carbon felt pressure sensors are synthesized via a one‐step hydrothermal method with further annealing. Carbon felt surface has a rich microstructure, which can increase the contact resistance with the electrode. Metal oxides are used as spacers for carbon fibers. Pressure sensors achieve low initial current without loading and high output current under loading, respectively, thus achieving excellent performance.